Obtaining biocompatible ceramic scaffolds of calcium phosphates through ceramic stereolithography - Carolina Duque-Uribe; Valentina López Vargas; Ana Isabel Moreno Florez; Alejandro Pelaez-Vargas; Alex Ossa; Carolina Cárdenas-Ramírez; Sebastián Restrepo-Vélez; Andrés Felipe Vásquez; Claudia Garcia (Journal of Materials Science: Materials in Medicine)
Abstract Ceramic stereolithography scaffolds with designs based on triple periodic minimal surfaces (TPMS) were developed for potential applications in bone tissue regeneration. An acrylic-based resin with calcium phosphate nanoparticles were used. Particles were synthesized via Combustion in solution, resulting in hydroxyapatite and β-TCP phases. Suspensions with 35, 40, and 50 vol% particles, using a 10 wt% of dispersant, were prepared and rheologically characterized to ensure suitable viscosities for printing, and were used to print gyroid scaffolds by DLP technique. The suspension with the highest ceramic load demonstrated the highest viscosity. The green bodies were morphologically and mechanically characterized before and after sintering. Volumetric shrinkage, morphological characteristics by digital and FE-SEM images, and compressive strength were evaluated. Polymeric-ceramic (Hybrid) scaffolds before sintering exhibited better compressive strength than sintered ones. Ceramic scaffolds achieved compressive strength values up to 0.9 MPa, comparable to those of cancellous and cortical bone. The optimal scaffolds (50CPF) were subjected to degradation tests in PBS and were impregnated with ethanolic extract of propolis from Arauca, Colombia, for biological analysis using the L929 cell line. The results indicate that ceramic stereolithography is an effective technique to produce scaffolds with optimal characteristics for potential applications in bone tissue regeneration. Graphical Abstract